Key factor driving coastal governance policy in Indonesia from a knowledge-based governance perspective - Laila, Elvi Nur Nujumul; Suryawati, Dina; Negoro, Abul Haris Suryo; Handika, Yola Rezki; Maulana, Muhammad Iqbal (Priviet Social Sciences Journal, 2025)
Coastal governance policies in Indonesia have undergone significant changes over time, influenced by dynamic knowledge development. This study aims to analyze the dynamics of coastal and small island governance policies in Indonesia using a Knowledge-Based Governance approach. The method used was qualitative content analysis of 67 regulations issued by the Indonesian government between 1960 and 2024. The results show that the knowledge gained in coastal zone management comes mostly from reflections on the past and the present. Dialectical learning involving public consultation and discussions among stakeholders is limited and has not been widely implemented. Co-evolution, in which stakeholders, knowledge, and institutions interact dynamically, is a key factor in creating policies that are responsive to environmental challenges. This study suggests that the government strengthen inter-agency coordination and increase the participation of the community and relevant parties in the decision-making process. This is useful for creating policies that are more flexible and adaptive to changes. Therefore, it is important to integrate learning that involves various perspectives to produce policies that are more innovative, comprehensive, and in line with the needs of Indonesia's coastal communities.